Pengaruh Edukasi Permainan Monopoli Demam Berdarah Terhadap Peningkatan Pengetahuan dan Perilaku Anak Usia Sekolah Dalam Pencegahan Demam Berdarah - Sh, Sugiharto; Arista, Amelya Putri (LPPM UNIKAL, 2024)
The objective of this study is to evaluate the effectiveness of the Dengue Fever Monopoly game as a learning media in improving knowledge and behavior related to the 3M Plus method for dengue fever prevention. The research method used is a quasi-experiment with a one-group pre- and post-test design. The sampling technique used is total sampling, where all 5th-grade elementary school students were included as study participant. Knowledge was assessed using a questionnaire, with the average scores analyzed and compared before and after the health education intervention. Meanwhile, behavior was analyzed by directly observing the implementation of dengue fever prevention using the 3M Plus method. In this study, 25 students participated, with an average age of 11 years, and 56% of the participants were male. The results showed that there was an increase in children's knowledge about dengue fever, as well as a change in their behavior regarding its prevention. Therefore, it can be concluded that the educational game